Potential of Turmeric (Curcuma Longa) in Increasing Hemoglobin Levels: Systematic Literature Review - Nadirah, Siti; Mulyantoro, Donny Kristanto; Wahyuni, Sri (STRADA : Jurnal Ilmiah Kesehatan, 2020)
According to WHO, 30% of the world's population is anemic, 27% of anemia occurs in developing countries and 6% occurs in developed countries. The handling of anemia by the government has not been maximized so that companion therapy is needed. Objective: To see the potential of turmeric (curcuma longa) to increase hemoglobin. Methods: Search methods from Scopus, Pubmed, Elsevier, Willy and Google Scholar. Published 2010 2020. RCT research with prism technique. Analysis of 25 articles related to blood loss diseases. 2 articles on hemodialysis patients, 7 articles on thalassemia patients, 3 NAFLD patients, 4 ulcerative colitis patients, 1 prehypertension patient, 3 diabetes patients, 1 metabolic syndrome patient, 1 alanine transaminase elevated patient, 2 arthritis patients and 1 breast cancer patient. There are only 3 articles that show an increase in Hb levels, so it can be concluded that curcuma longa is not effective in increasing hemoglobin levels.